Visual tracking of a moving target in 360-degree virtual reality: Analysis of the effects on attention and mood - Sellner, T.; Ehmann, P.; Spielmann, J.; Gogolla, F.; Rösgen, A.; Mayer, J.; Schoenfeld, M. A.; Flor, H. (Frontiers in Virtual Reality, 2025)
The training of attentional capacities is an important part of many rehabilitative efforts, for example, in the treatment of stroke. The Helix-Arena is an innovative virtual reality (VR) training device, which enables multimodal training in a 360-degree virtual environment. A pursuit training was developed for the Helix-Arena. In this study, we evaluate the effectiveness of the pursuit training in the Helix-Arena compared to a control group [CG, training on a personal computer (PC)] in 34 healthy participants. The experimental group (EG, N = 19) participated in four training sessions in the Helix-Arena over a period of 2 weeks. The control group (N = 15) completed similar training sessions in a non-VR environment on a PC. During each training session, changes in attention (Test of Attentional Performance battery, TAP) and general mood (Positive and Negative Affect Schedule, PANAS) were assessed pre- and post-training. A significantly higher pre-to-post improvement was observed in the EG for the TAP subtest attention shift in the subcategory invalid instructor (p = 0.04) than that in the CG. In addition, we found a higher positive affect after the training in the EG but not in the CG (p < 0.01). These results suggest advantages of the VR environment for attentional and affective processes. The VR training can thus improve not only cognitive abilities but also training motivation. In a next step, the training can be used with patients in a rehabilitation context, but it is also suitable for educational and gaming contexts.